ANALISIS RASIO KEUANGAN APBD UNTUK MENILAI KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN DHARMASRAYA - Dwi Lafia; Umiyati, Etik; Nurjanah, Rahma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the development of the Regional Revenue and Expenditure Budget (APBD) and evaluate the financial performance of the Dharmasraya Regency Government during 2015–2024 through financial ratio analysis. The study used secondary time series data from the Regional Government Financial Report (LKPD) and Budget Realization Reports (LRA) of Dharmasraya Regency and applied a descriptive qualitative method. The results showed that APBD development fluctuated during the period. The regional financial independence ratio was 10.56 percent (very low), indicating strong dependence on central transfers. The PAD effectiveness ratio was 93.21 percent (moderately effective), while the financial efficiency ratio was 89.61 percent (moderately efficient). The fiscal decentralization ratio was 9.31 percent (very poor). The operational expenditure harmony ratio reached 76.01 percent (good), whereas the capital expenditure harmony ratio was 23.50 percent (poor). In addition, the PAD growth ratio was 9.72 percent (low). Overall, the financial performance of Dharmasraya Regency still needs improvement through PAD optimization.